Silaturahmi dan Gandong: Rekonstruksi Eklesiologi melalui Perspektif Teologi Rahim C.S. Song - Michael Bryan; Justitia Vox Dei Hattu (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
Abstract. This article is an effort to reconstruct ecclesiology by discussing the value of silaturahmi from an Islamic perspective and the Gandong system in Maluku culture with the help of Choan Seng Song's womb theology as the theological lens. This effort was motivated by the 1999 conflict on Haruku Island which began with the conflict on Ambon Island which had damaged the fraternal relations between Christians and Muslims on Haruku Island. Meanwhile, traditional ecclesiology, because it emphasizes the superiority of the church, often makes conflicts even sharper. The results of this study show that both silaturahmi and Gandong emphasize fraternarly love which is addressed both internally and externally. These two elements are also conceived in Jesus' messianic movement, thus making it to be a relevant ecclesiology for the solution to the conflict that occurred.Abstrak. Artikel ini merupakan suatu upaya untuk merekonstruksi eklesiologi dengan mendialogkan nilai silaturahmi dari perspektif Islam dan sistem Gandong dalam kebudayaan Maluku dengan bantuan teologi rahim dari Choan Seng Song sebagai lensa teologisnya. Upaya ini dilatarbelakangi oleh adanya konflik tahun 1999 di Pulau Haruku yang berawal dari konflik di Pulau Ambon yang telah merusak relasi persaudaraan umat Kristen dan umat Islam di Pulau Haruku. Sementara itu, eklesiologi tradisional oleh karena lebih menekankan pada superioritas gereja seringkali justru menjadikan konflik semakin tajam. Hasil kajian ini menunjukkan bahwa baik silaturahmi maupun Gandong menekankan kasih persaudaraan yang ditujukan baik secara internal maupun eksternal. Kedua unsur ini juga terkandung dalam gerakan mesianik Yesus sehingga menjadikannya sebagai eklesiologi yang relevan bagi solusi atas konflik yang terjadi.